Americus, Lyon County - Ladd, Halston (Kansas State University, The Chapman Center for Rural Studies, 2012)
This essay portrays the founding of Americus, Kansas, and how it became one of the proudest populations in late 19th century Kansas. Through the ambitions of Arthur Baker, and the other fifteen members of the Americus Town Company, Americus thrived. This study includes early maps of Americus, articles from the town newspaper, and photographs of Americus town site.
Halston Ladd, “Americus, Lyon County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/100.
Keywords: Americus; Judge Arthur Ingram Baker; Breckenridge County; Lyon County; Automobile; Neosho River